Challenges for graduate students' mentors during COVID‐19 pandemic. Issue 6 (14th August 2021) - Li, Honglin; Zhang, Dake; Liang, Boying; Zhong, Lichao; Cao, Yue; Shen, Jie
Abstract: The outbreak of COVID‐19 pandemic results in the suspension of universities' academic laboratory activities. This brought a difficult time for graduate students majored in molecular biology and their mentors, since the student's thesis progress relies on the data from wet experiments in the lab. Even facing the challenges during the pandemic, mentors could still play an active role. This COVID‐19 crisis requires mentors to have more thinking, innovation, and sharing in guiding graduate students.